Design of Gasifier with Microwave-Based Technology with Steam and CO2 As Gas Agent To Produce Syngas - Imron Rosyadi; Shofiatul Ula; Rivaldi; Kurniawan Putra Yudha (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2022)
This research is motivated by the increasing gas emissions produced by industrial, automotive and household activities which mostly use fossil energy as an energy source. CO2 capture is introduced to the use of gasification technology in an effort to reduce CO2 emissions which are one of the causes of the greenhouse effect. The role of microwave is also introduced as an effort to increase thermal efficiency and increase production and quality of syngas and its role in reducing tar which is known to be high in biomass gasification. The utilization of water vapor is also clearly disclosed and its effect on syngas products, especially hydrogen gas. The role of the parameters that affect the gasification process is analyzed to see which variant has the best role in improving the quality and quantity of syngas. Research development opportunities are presented by looking at research gaps and future prospects